Effect of Rheum ribes L. pulp enriched with eugenol or thymol on survival of foodborne pathogens and quality parameters of chicken breast fillets - Karatepe, Pinar; Akgol, Muzeyyen; Tekin, Ali; Calicioglu, Mehmet; Incili, Gokhan Kursad; Hayaloglu, Ali Adnan (Elsevier, 2024)
The aim of this study was to characterize the pulp of Rheum ribes L. and to determine the effect of the pulp enriched with eugenol (1 %) or thymol (1 %) on the microbiological and physico-chemical quality of chicken breast fillets. Chicken breast fillets, inoculated with Listeria monocytogenes, Salmonella enterica subsp. enterica serovar Typhimurium, and Escherichia coli O157:H7 (similar to 6.0 log(10)), were marinated for 24 h in a mixture prepared from a combination of Rheum ribes L. pulp with eugenol or thymol. The quality parameters were analyzed for 15 days at +4 degrees C. The Rheum ribes L. pulp was found to have high antioxidant activity, high total phenolic content and contained 22 different phenolic substances, among which rutin ranked first. The pulp contained high levels of p-xylene and o-xylene as volatile substances and citric acid as an organic acid. The combination of Pulp + Eugenol + Thymol (PET) reduced the number of pathogens in chicken breast fillets by 2.03 to 3.50 log(10) on day 0 and by 2.25 to 4.21 log(10) on day 15, compared to the control group (P < 0.05). The marinating treatment significantly lowered the pH values of fillet samples on the first day of the study, compared to the control group (P < 0.05). During storage, TVB-N levels showed slower increase in the treatment groups compared to the control group (P < 0.05). In addition, the marinating process led to significant changes in physicochemical parameters such as water holding capacity, color, texture, cooking loss, and drip loss compared to the control group (P < 0.05). In conclusion, the results of this study showed that the pulp of Rheum ribes L., which has a high antioxidant capacity and contains various bioactive compounds. Furthermore, S. Typhimurium, E. coli O157:H7 and L. monocytogenes were inhibited considerably by marinating Rheum ribes L. pulp with a combination of eugenol and thymol.
Keywords: Rheum ribes L. pulp; Rhubarb; Eugenol; Thymol; Marination; Chicken breast fillet; Antibacterial activity